Genome and Transcriptome Sequences Reveal the Specific Parasitism of the Nematophagous Purpureocillium lilacinum 36-1 - Xie, Jialian; Li, Shaojun; Mo, Chenmi; Xiao, Xueqiong; Peng, Deliang; Wang, Gaofeng; Xiao, Yannong (Frontiers in Microbiology, 2016)
Purpureocillium lilacinum is a promising nematophagous ascomycete able to adapt diverse environments and it is also an opportunistic fungus that infects humans. A microbial inoculant of P. lilacinum has been registered to control plant parasitic nematodes. However, the molecular mechanism of the toxicological processes is still unclear because of the relatively few reports on the subject. In this study, using Illumina paired-end sequencing, the draft genome sequence and the transcriptome of P. lilacinum strain 36-1 infecting nematode-eggs were determined. Whole genome alignment indicated that P. lilacinum 36-1 possessed a more dynamic genome in comparison with P. lilacinum India strain. Moreover, a phylogenetic analysis showed that the P. lilacinum 36-1 had a closer relation to entomophagous fungi. The protein-coding genes in P. lilacinum 36-1 occurred much more frequently than they did in other fungi, which was a result of the depletion of repeat-induced point mutations (RIP). Comparative genome and transcriptome analyses revealed the genes that were involved in pathogenicity, particularly in the recognition, adhesion of nematode-eggs, downstream signal transduction pathways and hydrolase genes. By contrast, certain numbers of cellulose and xylan degradation genes and a lack of polysaccharide lyase genes showed the potential of P. lilacinum 36-1 as an endophyte. Notably, the expression of appressorium-formation and antioxidants-related genes exhibited similar infection patterns in P. lilacinum strain 36-1 to those of the model entomophagous fungi Metarhizium spp. These results uncovered the specific parasitism of P. lilacinum and presented the genes responsible for the infection of nematode-eggs.